Stress in yeasts and filamentous fungi - Avery, Simon V.; Stratford, Malcolm; West, P. van (Pieter) (British Mycological Society symposium series, 2008)
Yeasts and filamentous fungi need to cope with stress, whether growing in the laboratory or in the natural environment, whether victims or offenders in interactions with other organisms. These considerations are discussed in this volume that coveres stress in the broad sense, within the context of mycology. * Includes discussions of the stresses associated with organism-organism interactions and stress under controlled conditions * Anthropogenic stress towards fungi in the environment and the impacts that such stressors may have on different organisms and communities in the wild are explained * Encompasses a breadth of information from the bigger picture of stress effects on fungi in their natural habitats, to the recent advances in underlying molecular-level understanding.